Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1113/ep085449
|View full text |Cite
|
Sign up to set email alerts
|

Mild dehydration modifies the cerebrovascular response to the cold pressor test

Abstract: New Findings r What is the central question of this study?The cold pressor test (CPT) is commonly used to investigate cerebrovascular regulation. Despite blood viscosity per se being able to modulate cerebral blood flow, it is unknown whether hydration status alters this response, nor is it commonly reported. We investigated the effects of mild dehydration on the cerebrovascular response to the CPT. r What is the main finding and its importance?The main finding from this study is that when compared with euhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 52 publications
(118 reference statements)
2
41
0
Order By: Relevance
“…A recent study investigated the effects of hydration status on the middle cerebral artery mean blood velocity (MCAv) response to CPT and found that MCAv increased during CPT, but this response was attenuated in dehydrated individuals (Perry et al . ). The authors speculated that their results were attributed to a hyperventilation‐related reduction in P ET ,CO2, probably because of an elevated pain response in the dehydrated individuals (Perry et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study investigated the effects of hydration status on the middle cerebral artery mean blood velocity (MCAv) response to CPT and found that MCAv increased during CPT, but this response was attenuated in dehydrated individuals (Perry et al . ). The authors speculated that their results were attributed to a hyperventilation‐related reduction in P ET ,CO2, probably because of an elevated pain response in the dehydrated individuals (Perry et al .…”
Section: Introductionmentioning
confidence: 97%
“…The authors speculated that their results were attributed to a hyperventilation‐related reduction in P ET ,CO2, probably because of an elevated pain response in the dehydrated individuals (Perry et al . ). However, their assessment of CBF was only done in the middle cerebral artery (MCA) using transcranial Doppler ultrasound (TCD) and P ET ,CO2 was not controlled, and emerging evidence suggests that TCD may not be a valid measurement of CBF during increased MAP and SNA (Verbree et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…With respect to the latter, Ogino and collaborators (59) demonstrated that dehydration, in control subjects, leads to increased brain activity in the anatomical structures involved in pain perception (ACC, insula, and thalamus). Thus, dehydration may per se constitute a source of pain in healthy subjects (60). Furthermore, Perry et al (60) reported that hydration status is an important modulator of the cerebrovascular response to cold pressor tests, which are commonly used to investigate cerebrovascular regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, dehydration may per se constitute a source of pain in healthy subjects (60). Furthermore, Perry et al (60) reported that hydration status is an important modulator of the cerebrovascular response to cold pressor tests, which are commonly used to investigate cerebrovascular regulation. Therefore, dehydration may not only constitute a source of pain but also interfere with the ability to assess a nociceptive response in the patient.…”
Section: Resultsmentioning
confidence: 99%